Effects of cutting length and bud removal on root yield and starch content of cassava under rainfed conditions - Prasitsarn, Mapita; Polthanee, Anan; Trelo-ges, Vidhaya; Simmons, Robert W. (Cambridge University Press, 2017)
Bud removal of the cuttings at underground level has been claimed by cassava growers in Thailand as a method to increase cassava yield. This practise should be tested experimentally to explain the reason for yield increase. The objective of this study was to investigate the effects of bud removal and cutting length on storage root yield and starch content of three cassava varieties. Field experiment was conducted in a split–split plot design with four replications in 2010 and 2011, under rainfed conditions. Three cassava varieties (KU50, RY9 and HB60) were assigned as main plot. Two cutting lengths (15 cm and 30 cm) were assigned as sub plots, and two treatments of buds (buds cut and not cut) were assigned as sub–sub plots. The buds on the cuttings that were inserted into the soil were removed. In 2010, the plants from 15-cm long cuttings subjected to bud removal had higher fresh storage root yield (88.4 Mg ha−1) than did plants from 30-cm long cuttings subjected to bud removal (75.8 Mg ha−1). Cutting of buds also had higher fresh storage root yield (89.1 Mg ha−1) than did non bud-cutting (75.0 Mg ha−1). KU50 had the highest fresh storage root yield (91.4 Mg ha−1), dry root yield (48.4 Mg ha−1) and starch yield (20.1 Mg ha−1). Cutting length of 15 cm had higher starch concentration in storage roots (25.6%) than did cutting length of 30 cm (24.2%). HB60 had the highest starch concentration (27.0%) among cassava varieties tested. The data in 2011 were similar to the data in 2010. The responses of varieties to bud removal and cutting length are discussed.
Keywords: bud removal; cutting length; farmers' practice; root yield